Utilizing the Technology Acceptance Model (TAM) to Drive E-Warehouse Adoption in Brebes' Shallot Sector - Ade Yanyan Ramdhani; Muhammad Iqbal Faturohman; Lina Fatimah Lishobrina; Faizah; Alon Jala Tirta Segara; Arief Rais Bahtiar; Dimas Fanny Hebrasianto; Muhammad Alim Safa’at; Destyana Chandra Priyambodo; Diva Angelica; Rafli Dhafin Kamil; Farhan Aryo Pangestu (Politeknik Piksi Ganesha Indonesia, 2026)
This study explores the factors influencing the adoption of SiJuna, a cold storage-based e-warehouse platform, among shallot farmers in Brebes Regency. Price volatility significantly impacts farmers, leading to economic losses, particularly when prices drop below production costs. SiJuna aims to help farmers by offering cold storage to preserve their harvests during price declines and sell when prices stabilize. Using the Technology Acceptance Model (TAM), data was collected from 90 farmers and analyzed through Structural Equation Modeling (SEM). The results reveal that perceived ease of use and perceived usefulness positively influence farmers' behavioral intention to adopt SiJuna, which in turn significantly affects the actual use of the system. The findings underscore the importance of usability and perceived value in technology adoption, suggesting that a user-friendly design and clear benefits can enhance the adoption of agricultural technologies, ultimately improving post-harvest management and farmers' profitability.